PENDAMPINGAN PENGEMBANGAN MUTU PENYELENGGARAAN PESANTREN PADA LEMBAGA PENJAMINAN MUTU (LPM) PONDOK PESANTREN SALAFIYAH SYAFI’IYAH SUKOREJO - Maskuri Maskuri (As-Sidanah, 2019)
Abstract: Implementation of the boarding school from time to time to experience the dynamics of considerable interest to continue to be studied and explored. All schools in Indonesia continues to perform remediation efforts according to the times and the demands of society. It's time to make a breakthrough boarding innovative and creative in responding to the advancement of science and technology. As a user of the service organization of schools, the public has a "right" to provide corrections and contribute ideas for the development of quality schools. Because good and the quality of schools is closely related to public perception. In the context of understanding the dynamics of the development of schools to meet the needs of the service quality in order to produce good quality graduates, Boarding School in conjunction with the momentum Salafiyah Shafi'ites unification of universities in boarding schools, formed an organization that serves to accelerate the implementation of the quality of schools. The new institution called the Quality Assurance Agency Boarding School (Pesantren LPM) which is responsible to the Pesantren. Duties and functions are giving consideration to the development of quality caregivers for boarding. To know and understand how the LPM performance Pesantren, we perform community service through Pesantren LPM. Purpose and tujuannnya is providing assistance for the implementation of the vision and mission of the LPM, LPM know the planning and work, measures and follow-up activities, and how LPM involved in the process of quality development organization of schools. The new institution called the Quality Assurance Agency Boarding School (Pesantren LPM) which is responsible to the Pesantren. Duties and functions are giving consideration to the development of quality caregivers for boarding. To know and understand how the LPM performance Pesantren, we perform community service through Pesantren LPM. Purpose and tujuannnya is providing assistance for the implementation of the vision and mission of the LPM, LPM know the planning and work, measures and follow-up activities, and how LPM involved in the process of quality development organization of schools. The new institution called the Quality Assurance Agency Boarding School (Pesantren LPM) which is responsible to the Pesantren. Duties and functions are giving consideration to the development of quality caregivers for boarding. To know and understand how the LPM performance Pesantren, we perform community service through Pesantren LPM. Purpose and tujuannnya is providing assistance.